Merujuk Pasien STEMI: Kapan dan Kemana? - Kurniawan Agung Yuwono (Jurnal Kardiologi Indonesia, 2012)
Management of STEMI patients consist of initial recognition and diagnosis, early routine medication, and reperfusion therapy. Primary PCI has been set as default strategy for STEMI reperfusion in PCI-capable hospital. Unfortunately, only few STEMI patients can undergo primary PCI as reperfusion therapy, because the number of hospital with invasive capability is still low in many countries, including Indonesia. Because time is critical in reperfusion therapy, the emergency physicians in non-PCI capable hospital have to decide to hold or refer STEMI patients to a hospital with invasive capability. The reperfusion therapy options for STEMI patient presenting to a non-PCI capable hospital are fibrinolytic therapy, or refer to PCI-capable hospital, or both (pharmacoinvasive strategy). This review tried to summarize the evidences as a consideration in choosing the best reperfusion strategy for STEMI patients presenting to non-PCI capable hospital.